2021
DOI: 10.14202/vetworld.2021.3200-3210
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of biosynthetic gold nanoparticles on multidrug-resistant Escherichia coli and Salmonella species isolated from ruminants

Abstract: Background and Aim: Multidrug-resistant (MDR) pathogenic microorganisms have become a global problem in ruminants as a result of the intensive use of antibiotics, causing the development of resistance among gut microbiota. The antibiotic-resistant microorganisms can be transferred from diseased animals to humans. This study aimed to determine the prevalence of MDR Escherichia coli and Salmonella spp. isolated from cattle, buffaloes, sheep, and goats suffering from respiratory signs, diarrhea, and mastitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Moreover, the SEM displayed that the AgNPs have a spherical shape, while the AuNPs are rod-shaped, as reported in this research. Abdalhamed et al (2021a) examined AuNPs produced using phytochemicals for the green production of metallic NPs and found similar results to ours.. According to Nagar et al (2016), while bio-surfactants used to synthesize AgNPs alter the pH value and decrease their size (60 nm), nanoparticles are uniform at pH 9.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the SEM displayed that the AgNPs have a spherical shape, while the AuNPs are rod-shaped, as reported in this research. Abdalhamed et al (2021a) examined AuNPs produced using phytochemicals for the green production of metallic NPs and found similar results to ours.. According to Nagar et al (2016), while bio-surfactants used to synthesize AgNPs alter the pH value and decrease their size (60 nm), nanoparticles are uniform at pH 9.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, using NPs (nanoparticles) offers a solid policy to cope with infections and diseases triggered by MDR bacteria in animals (Farouk et al, 2020;Salah et al, 2020;Abdalhamed et al, 2021a;Masimen et al, 2022). Salah et al (2020) reported AgNPs exhibited a robust bactericidal influence against S. aureus isolated from mastitic ewes and goats.…”
mentioning
confidence: 99%
“…A methanol extract of the fruit mesocarp of Balanites aegyptiaca was used to synthesize gold (Au) nanoparticles with slight modifications to the method described earlier. 43,44 Freshly collected Balanites aegyptiaca fruits were thoroughly washed under tap water followed by double-distilled water. For the preparation of the extract, the washed fruits were peeled, and the mesocarp was separated from the fruits.…”
Section: Methodsmentioning
confidence: 99%
“…The size of gold-nanoparticles ranged from 5 to 30 nm. They were prepared by adding 1% disodium citrate solution (w/v) added to 0.01% aqueous chloroauric acid solution (w/v) at 100°C for 5 min according to the protocol described by Abdalhamed et al ( 18 ), then gradually cooled, the pH of the solution was adjusted to 8.4, and then the solution was stored at 4°C in a dark bottle. Monoclonal antibody (Ab) (100 mg/ml) was added drop wise into a 10 ml solution.…”
Section: Methodsmentioning
confidence: 99%
“…The lateral flow test (LFT) is rapid diagnostic technique based on specific immune responses involving antigens and antibodies that does not necessitate any special. An antibody labeled with gold nanoparticles (GNP) placed in a dried state on fiber glass with the great sensitivity ( 18 ).…”
Section: Introductionmentioning
confidence: 99%